Języki pisarzy polskich i dwukulturowych, czyli na ile literatura polska była i jest wielokulturowa - Skwara, Marta (Postscriptum Polonistyczne, 2020)
The author of the article focuses on Polish writers that intentionally create their works simultaneously in Polish and in languages other than Polish, situating their creativity directly in European and world literature. She also discusses the case of bicultural authors whose creativity emanates from Polish culture but for whom Polish was only one of the languages they based their literature on. While listing such examples, the author considers the possibility of interpreting such works and placing them in the discourse of world literature.